Flame-made calcium phosphate nanoparticles with high drug loading for delivery of biologics - Tsikourkitoudi, Vasiliki (2020)
Nanoparticles exhibit potential as drug carriers in biomedicine due to their high surface-to-volume ratio that allows for facile drug loading. Nanosized drug delivery systems have been proposed for the delivery of biologics facilitating their transport across epithelial layers and maintaining their stability against proteolytic degradation. Here, we capitalize on a nanomanufacturing process famous for its scalability and reproducibility, flame spray pyrolysis, and produce calcium phosphate (CaP) nanoparticles with tailored properties. The as-prepared nanoparticles are loaded with bovine serum albumin (model protein) and bradykinin (model peptide) by physisorption and the physicochemical parameters influencing their loading capacity are investigated. Furthermore, we implement the developed protocol by formulating CaP nanoparticles loaded with the LL-37 antimicrobial peptide, which is a biological drug currently involved in clinical trials. High loading values along with high reproducibility are achieved. Moreover, it is shown that CaP nanoparticles protect LL-37 from proteolysis in vitro. We also demonstrate that LL-37 retains its antimicrobial activity against Escherichia coli and Streptococcus pneumoniae when loaded on nanoparticles in vitro. Therefore, we highlight the potential of nanocarriers for optimization of the therapeutic profile of existing and emerging biological drugs.